In Vitro Activity of Ceftolozane-Tazobactam Against Enterobacterales and Pseudomonas Aeruginosa Causing Urinary, Intra-Abdominal and Lower Respiratory Tract Infections in Intensive Care Units in Portugal: the STEP Multicenter Study - García-Fernández, S (2020)
The STEP surveillance study was designed to increase knowledge about distribution of multidrug-resistant (MDR) Enterobacterales and Pseudomonas aeruginosa in Portugal, focusing on the intensive care unit (ICU). Antimicrobial susceptibility of common agents was also evaluated and compared with that of one of the latest therapeutic introductions, ceftolozane-tazobactam (C/T). Clinical isolates of Enterobacterales (n=426) and P. aeruginosa (n=396) from patients admitted in Portuguese ICUs were included. Activity of C/T and comparators was investigated using standard broth microdilution. Isolates were recovered from urinary tract (UTI, 36.9%), intra-abdominal (IAI, 24.2%) and lower respiratory tract (LRTI, 38.9%) infections. In P. aeruginosa, overall distribution of MDR/extremely-drug resistant (XDR)/pan-drug resistant (PDR) isolates accounted for 21.2%, 23.2% and 0.8%, respectively. C/T was the most potent agent tested against P. aeruginosa and MDR/XDR/PDR phenotypes. In Escherichia coli, extended-spectrum beta-lactamases (ESBL) and carbapenemase (CP) phenotypes accounted for 16.6% and 1.7%, respectively, whereas in Klebsiella spp., ESBL and CP-phenotypes represented 28.5% and 17.9%, respectively. Overall, susceptibility of C/T against Enterobacterales was 86.9%. C/T was the least affected agent in E. coli (99.4% susceptibility), whereas its activity was moderate in Klebsiella spp. (71.5%) and Enterobacter spp. (70.4%), due in part to a high rate of ESBL and CP-phenotypes. In Enterobacterales, blaKPC was the most prevalent CP gene (63.0%), followed by blaOXA-48 (33.3%) and blaVIM (3.7%). These microbiological results reinforce C/T as a therapeutic option in ICU patients with UTI, IAI or LRTI due to P. aeruginosa or Enterobacterales isolates, but not for CP producers.